In Vitro Activity of Nisin A Against Staphylococci Isolated from Periprosthetic Joint Infection - Melissa J. Karau; Christina A. Koscianski; Andrew D. Badley; Nicholas A. Bedard; John W. Zinckgraf; Robin Patel (Antibiotics)
Background/Objectives: Staphylococci are the most common causes of periprosthetic joint infection (PJI); new antimicrobials are needed to manage these difficult infections. Nisin A is a lantibiotic peptide derived from Lactococcus lactis that has antimicrobial activity against Gram-positive bacteria, including staphylococci, and is an FDA-approved preservative used in the food and dairy industry. Here, the in vitro nisin A susceptibility of PJI-associated staphylococci was assessed. Methods: The minimum inhibitory concentrations (MICs), minimum biofilm inhibitory concentrations (MBICs), and minimum biofilm bactericidal concentrations (MBBCs) of nisin A were measured by broth microdilution against 106 staphylococcus isolates isolated from PJI. MICs were assessed using 5 × 105 CFU/mL plus nisin A. For MBICs, biofilms were grown on pegged lids for 6 h, followed by 20 h of treatment. For MBBCs, pegged lids were transferred to plates containing media only for 20 h. The results were determined as the lowest concentrations with no visual growth. Two-dimensional MICs with nisin A and vancomycin were assessed for 20 isolates. Fractional inhibitory concentrations (FICs) were calculated to determine synergistic, additive, antagonistic, or indifferent interactions. Results: The MIC that inhibited 90% of S. aureus and S. epidermidis was 4 µg/mL, apart from for the MRSA subset (8 µg/mL). The MBIC that inhibited 90% of isolates was 4 µg/mL. The MBBCs ranged from 4 to 256 µg/mL. When tested together, nisin A and vancomycin yielded an FIC between 1.25 and 1.5, indicative of indifference, except for one isolate each of MRSA and MSSA, for which an additive effect (FIC of 1) was observed. Conclusions: Nisin A showed inhibitory activity against staphylococci that cause PJI.